2014
DOI: 10.1038/nature13543
|View full text |Cite
|
Sign up to set email alerts
|

Molecular architecture and mechanism of the anaphase-promoting complex

Abstract: The ubiquitination of cell cycle regulatory proteins by the anaphase-promoting complex/ cyclosome (APC/C) controls sister chromatid segregation, cytokinesis and the establishment of G1. The APC/C is an unusually large multimeric cullin-RING ligase. Its activity is strictly dependent on regulatory coactivator subunits that promote APC/C -substrate interactions and stimulate its catalytic reaction. Because the structures of many APC/C subunits and their organization within the assembly are unknown, the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
368
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(383 citation statements)
references
References 68 publications
(112 reference statements)
13
368
1
1
Order By: Relevance
“…A study using TAP-MS in Arabidopsis cell suspension cultured cells identified at least 11 APC subunits (Capron et al 2003;Van Leene et al 2010). Three dimensional reconstruction of human APC has shown that the complex adopts a triangular shape, a bit similar-looking as an open shell (Chang et al 2014). The backbone contains a lobe of tetratricopeptide (TPR) domain-containing subunits APC3, APC6, APC7 and APC8, and a platform built out of APC1, APC4 and APC5.…”
Section: Apcmentioning
confidence: 99%
“…A study using TAP-MS in Arabidopsis cell suspension cultured cells identified at least 11 APC subunits (Capron et al 2003;Van Leene et al 2010). Three dimensional reconstruction of human APC has shown that the complex adopts a triangular shape, a bit similar-looking as an open shell (Chang et al 2014). The backbone contains a lobe of tetratricopeptide (TPR) domain-containing subunits APC3, APC6, APC7 and APC8, and a platform built out of APC1, APC4 and APC5.…”
Section: Apcmentioning
confidence: 99%
“…Previous cryo-EM studies showed that Cdh1 association with the APC/C promotes substantial conformational changes in the catalytic module and the neighboring platform subunits Apc1, Apc4, and Apc5 (12). This change in conformation exposes the UbcH10-binding site of the catalytic module, enhancing UbcH10 association and thereby stimulating APC/C E3 ligase activity (12,19).…”
Section: Significancementioning
confidence: 99%
“…APC/C activity is controlled by its association with one of two coactivator subunits (either Cdc20 or Cdh1) that function to specify substrate recognition and stimulate ubiquitin transfer reactions (11)(12)(13)(14). The mitotic coactivator Cdc20 preferentially binds to hyperphosphorylated APC/C, whereas Cdh1 also binds to unphosphorylated APC/C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cdc20 is replaced by Cdh1 later in mitosis in somatic cell cycles. Cdc20 and Cdh1 bind reversibly to the APC/C and, in doing so, activate it by changing its conformation to reposition APC11 to recruit the E2 enzyme in closer proximity to the bound substrate (Chang et al 2014). Cdc20 and Cdh1 are WD40 family members and the aminoterminal residues of the D-box bind between blades 1 and 7 of the WD40 domain; the carboxy-terminal residues bind to APC10 (He et al 2013).…”
Section: Sister Chromatid Separationmentioning
confidence: 99%